Pain and Physical Functioning in Neuropathic Pain: A Systematic Review of Psychometric Properties of Various Outcome Measures. Issue 4 (10th April 2015) - Mehta, Poonam; Claydon, Leica S.; Hendrick, Paul; Cook, Chad; Baxter, David G.
Abstract: Introduction: A range of outcome measures across various domains are used to evaluate change following an intervention in clinical trials on chronic neuropathic pain (NeP). However, to capture a real change in the variable of interest, the psychometric properties of a particular measure should demonstrate appropriate methodological quality. Various outcome measures in the domains of pain and physical functioning have been used in the literature for NeP, for which individual properties (eg, reliability/validity) have been reported. To date, there is no definitive synthesis of evidence on the psychometric properties of those outcome measures; thus, the aim of this systematic review was to evaluate the methodological quality [COnsensus‐based Standards for the selection of health status Measurement INstruments (COSMIN) guidelines] of studies that evaluated psychometric properties of pain and physical functioning outcome measures used for NeP. Methods: Specific MeSH/keywords related to 3 areas (pain and/or physical functioning, psychometric properties, and NeP) were used to retrieve relevant studies (English language) in key electronic databases (MEDLINE (Ovid), CINAHL (EBSCO), Scopus, AMED, and Web of Science) from database inception—July 2012. Articles retrieval/screening and quality analysis (COSMIN) were carried out by 2 independent reviewers. Results: Twenty‐four pain and thirty‐seven physical functioning outcome measures were identified, varying in methodological quality from poor–excellent. Conclusion: Although a variety of pain and physical functioning outcome measures have been reported in the literature, few have demonstrate methodologically strong psychometric properties. Thus, future research is required to further investigate the psychometric properties of existing pain and physical functioning outcome measures used for clinical and research purposes.